Crosstalk between ferroptosis and steroid hormone signaling in gynecologic cancers - Lai, Wen; Chen, Jianquan; Wang, Tianming; Liu, Qiaoling (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is a novel types of regulated cell death and is widely studied in cancers and many other diseases in recent years. It is characterized by iron accumulation and intense lipid peroxidation that ultimately inducing oxidative damage. So far, signaling pathways related to ferroptosis are involved in all aspects of determining cell fate, including oxidative phosphorylation, metal-ion transport, energy metabolism and cholesterol synthesis progress, et al. Recently, accumulated studies have demonstrated that ferroptosis is associated with gynecological oncology related to steroid hormone signaling. This review trends to summarize the mechanisms and applications of ferroptosis in cancers related to estrogen and progesterone, which is expected to provide a theoretical basis for the prevention and treatment of gynecologic cancers.Ferroptosis occurs mainly by targeting two pathways (extrinsic and intrinsic pathways) (Tang, 2020). In the extrinsic pathway, ferroptosis begins with the inhibition of cystine/glutamic acid transporter (system xc−) or with the activity of the serotransferrin (TF)-mediated iron uptake. In the intrinsic pathway, it is activated by blocking intracellular antioxidant enzyme such as GPX 4 (Chen, 2021).System xc−-GSH-GPX4 pathway is the main defense system to antiferroptosis. The system xc− is comprised of two subunits: solute carrier family 7 member 11(SLC7A11) and solute carrier family 3 members 2 (SLC3A2) (Sato, 2000). After the exchange of Cysteine and Cystine, system xc− maintains the GSH generation in a continuous reactions (Lewerenz, 2013). In mammalian cells, one of the most important functions of system xc− is mediating Cystine transport by glutamate reverse transportation. Cystine is convert to cysteine, then cysteine is catalyzed by glutamate-cysteine ligase (GCL) and glutathione synthetase (GSS) for GSH synthesis (Bayır, 2020). SLC7A11 is commonly used as the target of system xc−. SLC7A11 promotes the expression of GPX4 through the mTORC-4EBP1 signaling pathway (Zhang, 2021). Up-regulating the expression of system xc− is involved in the enhanced chemoresistance and tumor growth (